2018
DOI: 10.5114/fmpcr.2018.78252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergy in children with adenoid hypertrophy and otitis media with effusion admitted to the Department of Pediatric Otolaryngology in Poznan

Abstract: Background. allergic diseases are the most common chronic illnesses in children. it is said that patients with allergy more often suffer from adenoid hypertrophy and otitis media with effusion than non-allergic patients. Objectives. to estabilish the prevalence of allergy in children with adenoid hypertrophy with or without otitis media with effusion (oMe) admitted to the department of Pediatric otolaryngology in Poznan between 05.2017 and 05.2018 and to check if allergy affects the incidence of oMe and adenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…Studies have shown a possible relationship between AR and adenotonsillar hypertrophy (4). However, in Poland, Adamczyk et al evaluated allergy among 153 children diagnosed with adenotonsillar hypertrophy with or without otitis media from 2017 to 2018 and observed a higher prevalence of adverse effects in patients with adenotonsillar hypertrophy, compared to our study (16).…”
Section: Discussioncontrasting
confidence: 69%
“…Studies have shown a possible relationship between AR and adenotonsillar hypertrophy (4). However, in Poland, Adamczyk et al evaluated allergy among 153 children diagnosed with adenotonsillar hypertrophy with or without otitis media from 2017 to 2018 and observed a higher prevalence of adverse effects in patients with adenotonsillar hypertrophy, compared to our study (16).…”
Section: Discussioncontrasting
confidence: 69%